Nonprimary Maternal Cytomegalovirus Infection After Viral Shedding in Infants. Issue 7 (July 2018) - Boucoiran, Isabelle; Mayer, Bryan T.; Krantz, Elizabeth M.; Marchant, Arnaud; Pati, Sunil; Boppana, Suresh; Wald, Anna; Corey, Larry; Casper, Corey; Schiffer, Joshua T.; Gantt, Soren
Abstract : Background: Most infants with congenital Cytomegalovirus (CMV) infection are born to seropositive women as a result of maternal CMV nonprimary infection (reinfection or reactivation). Although infected children are known to transmit CMV to their seronegative mothers, the frequency and magnitude of nonprimary maternal CMV infection after exposure to viral shedding by children in their household have not been characterized. Methods: A cohort of Ugandan newborns and their mothers were tested weekly for CMV by quantitative polymerase chain reaction of oral swabs. Infant primary infection and maternal nonprimary infection were defined by the onset of persistent high-level oral CMV shedding. Strain-specific antibody testing was used to assess maternal reinfection. Cox regression models with time-dependent covariates were used to evaluate risk factors for nonprimary maternal infection. Results: Nonprimary CMV infection occurred in 15 of 30 mothers, all after primary infection of their infants by a median of 6 weeks (range: 1–10) in contrast to none of the mothers of uninfected infants. The median duration of maternal oral shedding lasted 18 weeks (range: 4–42) reaching a median maximum viral load of 4.69 log copies/mL (range: 3.22–5.64). Previous-week infant CMV oral quantities strongly predicted maternal nonprimary infection (hazard ratio: 2.32 per log10 DNA copies/swab increase; 95% confidence interval: 1.63–3.31). Maternal nonprimary infections were not associated with changes in strain-specific antibody responses. Conclusions: Nonprimary CMV infection was common in mothers after primary infection in their infants, consistent with infant-to-mother transmission. Because infants frequently acquire CMV from their mothers, for example, through breast milk, this suggests the possibility of "ping-pong" infections. Additional research is needed to characterize the antigenic and genotypic strains transmitted among children and their mothers. Abstract : Supplemental Digital Content is available in the text.